2021
DOI: 10.1038/s41366-021-00765-x
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing technological solutions for childhood obesity prevention and treatment: a systematic review and meta-analysis of current applications

Abstract: Background Technology holds promise for delivery of accessible, individualized, and destigmatized obesity prevention and treatment to youth. Objectives This review examined the efficacy of recent technology-based interventions on weight outcomes. Methods Seven databases were searched in April 2020 following PRISMA guidelines. Inclusion criteria were: participants aged 1–18 y, use of technology in a prevention/treatment intervention for overwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 103 publications
4
42
2
Order By: Relevance
“…Similar to our findings, the previous meta-analyses on the treatment of childhood obesity have not found a difference in treatment effect according to intervention duration. 97,100 However, a previous meta-analysis targeting technology-based interventions for prevention and treatment of obesity, 52 found that shorter duration interventions were associated with significant effect, which the authors argue that could be related to the issues of engagement and long-term adherence of digital interventions. 101 In our meta-analysis, none of the included studies recorded follow-up measurements after the end of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our findings, the previous meta-analyses on the treatment of childhood obesity have not found a difference in treatment effect according to intervention duration. 97,100 However, a previous meta-analysis targeting technology-based interventions for prevention and treatment of obesity, 52 found that shorter duration interventions were associated with significant effect, which the authors argue that could be related to the issues of engagement and long-term adherence of digital interventions. 101 In our meta-analysis, none of the included studies recorded follow-up measurements after the end of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…44 Systematic reviews have examined the effectiveness of e-health interventions, combining prevention and treatment of obesity in children. [48][49][50][51][52][53] However, just a few specifically focused on the treatment of obesity, defined as interventions which target only children with overweight and obesity rather than mixed weight. 54 The meta-analyses on e-health intervention for the treatment of overweight and obesity so far published do not limit the duration of the intervention delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little seems to be known about the impact of digital technologies on healthy eating/drinking, PA and the variety of movement in children, especially when being applied in the relevant settings of (early) childhood education. 30 45 50 51 An evidence-based and responsible implementation of digital primary prevention interventions in these settings may lead to an increased acceptance of educational staff and ultimately lay the foundations of digital interventions being also seen as facilitators of healthy lifestyles for children. 35 It is of vital importance to find out how settings like day-care facilities and primary schools can be adequately equipped, qualified and empowered to effectively and responsibly use digital interventions to support healthy behaviours of children.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, technology adjuncts to FBT have been shown to be feasible in children from low-income households, 20 and a recent meta-analysis suggests that technology-based/assisted treatment approaches for childhood obesity are effective. 21 Although possession and knowledge of use of technology to facilitate health information are not universal, households that have limited access to health care, for example, lowincome households, are more likely to rely solely on mobile devices for communication and Internet access, 22,23 suggesting the potential for mobile devices to be a viable method for service delivery, particularly when that service does not rely heavily on data usage. A digital treatment platform that can be accessed through any mobile or Internet-enabled device and provides easy access to digitized treatment materials and resources to support families in FBT (e.g., having mobile access to daily behavior tracking logs can reduce barriers to tracking and improve adherence) can also facilitate a continuous relationship between the provider delivering the treatment and the family outside of in-person treatment sessions, improving adherence to and sustained engagement with treatment.…”
Section: Individual-level: Fbtmentioning
confidence: 99%